Analisis Pengaturan Living Law dalam RUU KUHP yang Dituangkan pada Peraturan Daerah Ditinjau Berdasarkan Konstitusi - Aisha Nurul Fadilla; Defa An Nuur Kusumajakti; Rangga Maulana Fauzi (Faculty of Law, Universitas Airlangga, 2024)
Abstract The Draft Criminal Code Law (RUU KUHP) is a reformation of the criminal Code left behind with the aid of the Dutch East Indies colonial generation which became no longer in accordance with existence in society. Within the regulatory layout, residing law turns into an issue or new component that is accommodated as an implementation of the growth of the legality precept that is anticipated in order to assist law enforcement which is felt to be greater simply and bring continuity between (UU and residing law). That is realized through the existence of regional regulations as an expansion of the principle of legality which in its scope regulates the compilation of customary criminal offenses. However, this is felt to be inconsistent with Article 18B paragraph (2) of the 1945 constitution which regulates the recognition and appreciate for customary law and conventional rights. The inclusion of residing law preparations in regional regulations causes regulations regarding respect and also the conventional rights of Indigenous Peoples Abstrak Rancangan Undang-Undang Kitab Undang-Undang Hukum Pidana (RUU KUHP) merupakan pembaharuan KUHP peninggalan zaman kolonial Hindia Belanda dimana sudah tidak sesuai lagi dengan kehidupan yang ada di masyarakat. Dalam rancangan pengaturannya, living law menjadi sebuah isu ataupun hal baru yang diakomodir sebagai implementasi perluasan asas legalitas yang digadang-gadang dapat membantu penegakan hukum yang dirasa lebih adil dan membawa kesinambungan antara (UU dan living law). Hal tersebut diwujudkan dengan adanya Peraturan Daerah sebagai perluasan asas legalitas yang dalam cakupannya mengatur tentang kompilasi Delik pidana adat. Namun, hal tersebut dirasa tidak sejalan dengan Pasal 18B ayat (2) Undang- Undang Dasar 1945 yang mana mengatur mengenai pengakuan serta penghormatan hukum adat dan hak-hak tradisional. Dimasukkannya pengaturan living law dalam Peraturan Daerah menyebabkan adanya pembatasanpembatasan mengenai penghormatan dan juga hak-hak tradisional Masyarakat Hukum Adat.